Comparing Metabolic Pathways through Reactions and Potential Fluxes - Baldan, Paolo; Cocco, Nicoletta; Giummolè, Federica; Simeoni, Marta (Transactions on Petri Nets and Other Models of Concurrency VIII, 2013)
Comparison of metabolic pathways is useful in phylogenetic analysis and for understanding metabolic functions when studying diseases and in drugs engineering. In the literature many techniques have been proposed to compare metabolic pathways. Most of them focus on structural aspects, while behavioural or functional aspects are generally not considered. In this paper we propose a new method for comparing metabolic pathways of different organisms based on a similarity measure which considers both homology of reactions and functional aspects of the pathways. The latter are captured by relying on a Petri net representation of the pathways and comparing the corresponding T-invariant bases, which represent minimal subsets of reactions that can operate at a steady state. A prototype tool, CoMeta, implements this approach and allows us to test and validate our proposal. Some experiments with CoMeta are presented.